Membangun Jiwa Kewirausahaan Masyarakat Pekon Klaten Melalui Pemanfaatan Lahan Sempit - Lies Kumara Dewi; Eka Ubaya Taruna Rauf; Husna Purnama; Patoni Patoni (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This entrepreneurship program is to provide recommendations or alternative solutions to a problem how to build the entrepreneurial spirit of the community through the use of narrow land, namely hydroponic planting in Pekon Klaten, Gading Rejo District, Pringsewu Regency, Lampung Province. This partnership program activity aims to 1) Provide assistance to overcome problems that arise from the establishment of